2011
DOI: 10.1021/ma201847v
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity and Structural Defects in Model Hydrogels: A Combined Proton NMR and Monte Carlo Simulation Study

Abstract: We present a study of the structure of Tetra-PEG model networks, using proton multiple-quantum NMR at low field in combination with computer simulations. Tetra-PEG is a novel high-performance hydrogel designed by combination of two symmetric tetra-arm macromonomers. In contrast to conventional hydrogels, which are highly heterogeneous due to fixed concentration fluctuations, Tetra-PEG exhibits a much less heterogeneous microstructure as indicated by previous light and small-angle neutron scattering studies. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
277
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(301 citation statements)
references
References 43 publications
(99 reference statements)
17
277
1
4
Order By: Relevance
“…Experimental techniques such as rheology/spectroscopy and multiple-quantum NMR can provide semi-quantitative information related to the loop structure [31][32][33]. Recently, Zhou et al reported 'network disassembly spectrometry' (NDS), which is the first experimental method for directly quantifying primary loops [34,35].…”
mentioning
confidence: 99%
“…Experimental techniques such as rheology/spectroscopy and multiple-quantum NMR can provide semi-quantitative information related to the loop structure [31][32][33]. Recently, Zhou et al reported 'network disassembly spectrometry' (NDS), which is the first experimental method for directly quantifying primary loops [34,35].…”
mentioning
confidence: 99%
“…Unlike dangling chains, which can be readily quantified via titration or spectroscopy, there are no known methods for quantification of primary loops. Their prevalence is estimated from pregel measurements or variations between the properties of a given material and theoretical model networks (2,4,(7)(8)(9)(12)(13)(14)(15)(16)(17). These molecular-level mechanical imperfections could critically impact modern applications of polymer networks and gels (18-28), especially those built on an end-linked network architecture (29-33).…”
mentioning
confidence: 99%
“…Future studies could therefore consider realistically generated network samples by using molecular simulations to mimic the crosslinking process [61][62][63]. Ultimately, this and follow-up studies will provide guidance to the design and analysis of novel polymer networks with desirable super tensile properties.…”
Section: Discussionmentioning
confidence: 99%